Analisis Tingkat Literasi Keuangan Pengguna Fintech Payment OVO - Nur Anisah; Hizkia Franzias Crisnata (STIE PGRI Dewantara Jombang, 2021)
Knowledge of financial Management should be the basis for decision making for MSMEs in running their business. Supported by various regulations and facilities by the government and private sector, MSMEs should be able to make the best use of technology in accordance with their business needs. Fintech is a financial service that can help players to make payment transactions. This research uses descriptive qualitative method with the aim to find out the level of MSMEs financial literacy in Mojokerto City about Financial Technology (Fintech) Payment. Financial literacy has 4 levels: not literate, less literate, sufficient literate, well literate. Financial literacy is measured by indicators of knowledge, beliefs, features, benefits, risks, rights and obligations, and skills in using fintech payments. The key informants in this study are the owners of the MSMEs Paradox Cafe and John Like Bread in Mojokerto City who use fintech payment OVO in their business. The data analysis technique used in this study was triangulation. Based on the results of the interview it can be concluded that the Paradox Cafe and Bread of John Like Mojokerto City have a literacy level that is well literate because they have knowledge, beliefs, features, benefits, risks, rights and obligations, as well as skills in using fintech payment in managing financial transactions and in decision making for his efforts.